Developing Self-Knowledge and Occupation of Student with Physically Handicapped - Endang Pudjiastuti Sartinah (Journal of ICSAR, 2017)
This research aimed at describing the process of developing self-knowledge and occupation of student with physically handicapped. It started by identifying and doing needs assessment for the future career targets, planning the development progress of career guidance for them, drawing the quality of career guidances. The proceduere development od research adapts the theory by Brophy (2002), It’s consist are reaching and collection of information then the planning and development of products. The final product of the module with CIP models was revised as an attempt to develop the potential for future careers of student with physically handicapped.